Single Power-Conversion Ac–Dc Converter with High Power Factor Based On ZVZCS for Dc Drive Applications - Srisanthosh Kumar, S.; Emayavaramban, G.; Amudha, A.; Siva Ramkumar, M.; Viyathukattuva; Divyapriya, S. (International Journal of Psychosocial Rehabilitation, 2019)
Single power conversion AC to DC converter is proposed in this project. For output control and correction of power factor, novel control algorithm is used in proposed converter. Single power conversion is provided by this. In Continuous Conduction Mode (CCM) operation, non-minimum phase behavior is exhibited boost converter. With Proportional-Integral (PI) voltage controller, in a digitally current-mode controlled boost converter, non-linear tuning method is proposed in this paper. System performance is enhanced by combing zero current and voltage with proposed digital pulse with modulation. Soft witching is produced by zero current and voltage switching. Losses in switching is reduced by this and efficiency of system is enhanced by this. In MATLAB, simulated this boost converter. With maximum power factor, output is produced.